Efficient device engineering for inverted non-fullerene organic solar cells with low energy loss. Issue 16 (10th April 2018) - Xiao, Jingyang; Chen, Ziming; Zhang, Guichuan; Li, Qing-Ya; Yin, Qingwu; Jiang, Xiao-Fang; Huang, Fei; Xu, Yun-Xiang; Yip, Hin-Lap; Cao, Yong
Abstract : We have systematically investigated the synergistic effect of thermal annealing and interlayer modification on improving the performance of inverted non-fullerene organic solar cells. Abstract : In recent years, the use of non-fullerene acceptors in organic solar cells has rapidly advanced with new acceptor materials, which have enabled devices to achieve a power conversion efficiency greater than 13%. In addition to new acceptor materials' design, device engineering plays an important role in improving the device performance. In this study, we develop effective device engineering strategies, including thermal annealing and interlayer modification, to improve the device performance from 7.39% to 9.39%. With the use of PTB7-Th as the donor and IDT-BT-R as the non-fullerene acceptor, we achieved an efficient non-fullerene organic solar cell based on an inverted device architecture with a power conversion efficiency as high as 9.39%. It is worthy of note that the energy loss of the optimized device is only around 0.5 eV, which can be attributed to weak recombination and the appropriate high energy level of the charge transfer states within the optimized device.